Isolation and Structure Elucidation of Bioactive Compounds (Dedicated to the memory of the late Professor Charles D. Hufford) - Ilias, Muhammad (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
We are very pleased to introduce the Book Version of our Special Issue in Molecules dedicated to the memory of the late Professor Dr. Charles D. Hufford. The issue has been a huge success, with 22 full-length peer-reviewed papers and a tribute by Professor Alice M.Clark. Authors, reviewers, and collaborators from many countries across the worldhave contributed to this endeavour, and we are truly grateful to all. This Special Issue isrepresentative of the broad impact that “Charlie” had on the field of bioactive naturalproducts. This Special Issue comprises papers from Professor Hufford’s former students,colleagues, and collaborators throughout the world who have utilized a wide array ofstate-of-the-art techniques to examine diverse natural sources to isolate and identify avariety of natural products with a wide spectrum of biological activities, including somenew microbial transformations and insights into bioactive molecules. Many new bioactive compounds are described and reported here for the first time. Bioactivities reportedinclude cytotoxicity, antimicrobial activity, anti-inflammatory activity, antileishmanialactivity, antitrypanosomal activity, antimalarial activity, analgesic activity, and beneficialliver activities, just to name a few. This Special Issue will undoubtedly have a lasting impact on the field of bioactive natural products, as exemplified by the career of Dr. Hufford.Lastly, without the timely and outstanding contributions from all of you, this Special Issue would not have been possible. We thank you all very much for your contributions and your time devoted to this Special Issue in memory of a special person. Finally, we express ourgratitude and thanks to the journal Molecules and their excellent team of expert reviewers for giving us the support and opportunity to make this Special Issue a huge success!